Bilateral mesh denoising - Kosasih, Juan Antonio (2017)
In this project, bilateral filter adapted for mesh denoising has been implemented and specific metrics has been calculated during its runtime to analyse its complexity and accuracy. The implementation of bilateral filter for mesh denoising was achieved by filtering vertexes of a 3D model specified in M file by moving it in its normal direction according to neighbourhood vertexes. The algorithm ran in linear time with difference in mesh size, and in exponential time according to neighbourhood search ring size. Results suggested larger ring size does not increase accuracy nor performance of the algorithm. Smaller ring sizes were found to be more effective and faster for the execution of the algorithm.